Identifying Trends of Policy Transfer Practices in Indonesia: A Systematic Literature Review (2012 - 2022) - Yuniar Sani, Sofia; Fathurrahman, Reza (Asian Journal of Social and Humanities, 2023)
The practice of policy transfer has been known since 315 BC, but conceptually it has been increasingly discussed by policy experts in the world in the last 30 years. In the Indonesian context, the application of policy transfers has been increasingly adopted by policymakers in the last ten years or so. In practice, policy transfer is an alternative that makes it easier for policymakers to make new policies. Policy transfer facilitates learning of good policy practices from various initiating countries so as to minimize failure. The transfer process is easier to build when a network or relationship is established between the actors acting as the source of the transfer, the recipient of the transfer, or other related parties. This study analyzes the implementation of policy transfers that have occurred in Indonesia in the last ten years (2012-2022) through 4 stages of Systematic Literature Review, namely 1) Pre-SLR; 2) Identification, 3) Screening, and 4) Eligibility. There were 31 selected publications which were further analyzed based on three criteria: 1) Fields/areas where policy transfer was applied, 2) Research methods conducted, and 3) Policy transfer analysis. Topics related to the analysis of policy transfers produce 5 sub-topics that can be studied further, namely: Transfer products, Transfer Loci, Policy Actors, Forms of Transfers, and Transfer Processes